SAR Probing of KX2-391 Provided Analogues With Juxtaposed Activity Profile Against Major Oncogenic Kinases - Omar, Abdelsattar M.; Khayat, Maan T.; Ahmed, Farid; Muhammad, Yosra A.; Malebari, Azizah M.; Ibrahim, Sara M.; Khan, Mohammad I.; Shah, Dhaval K.; Childers, Wayne E.; El-Araby, Moustafa E. (Frontiers in Oncology, 2022)
Tirbanibulin (KX2-391, KX-01, Figure 1), a dual non-ATP (substrate site) Src kinase and tubulin-polymerization inhibitor, demonstrated a universal anti-cancer activity for variety of cancer types. The notion that KX2-391 is a highly selective Src kinase inhibitor have been challenged by recent reports on the activities of this drug against FLT3-ITD mutations in some leukemic cell lines. Therefore, we hypothesized that analogues of KX2-391 may inhibit oncogenic kinases other than Src. A set of 4-aroylaminophenyl-N-benzylacetamide were synthesized and found to be more active against leukemia cell lines compared to solid tumor cell lines. N-(4-(2-(benzylamino)-2-oxoethyl)phenyl)-4-chlorobenzamide (4e) exhibited activities at IC50 0.96 µM, 1.62 µM, 1.90 µM and 4.23 µM against NB4, HL60, MV4-11 and K562 leukemia cell lines, respectively. We found that underlying mechanisms of 4e did not include tubulin polymerization or Src inhibition. Such results interestingly suggested that scaffold-hopping of KX2-391 may change the two main underlying cytotoxic mechanisms (Src and tubulin). Kinase profiling using two methods revealed that 4e significantly reduces the activities of some other potent oncogenic kinases like ERK1/2 (>99%) and greatly upregulates the pro-apoptotic c-Jun kinase (84%). We believe that future optimizations may help to identify interesting new generation of anticancer agents based on the structure of 4-aroylamino-N-benzylarylacetamide as new pharmacophore against oncogenic kinases. We believe that future optimizations may help to identify interesting new generation of anticancer agents based on the structure of 4-aroylamino-N-benzylarylacetamide as new pharmacophore against oncogenic kinases.